Design and fabrication of low cost paddy thresher - BABU V SAISUNDAR S SUNILKUMAR PANDEY; Er. George Mathew (Guide) (Tavanur 1992 Kelappaji College of Agricultural Engineering and Technology)
efficient thresher. KCAET Tavanur product. spike type threshing drum, feeding chute, cylinder cover, blower and frame single person operated machine.single phase electric motor
Design and fabrication of low cost paddy thresher